Quandaries over the morphonology of the verb in modern standard Arabic and Tunisian Arabic: a tentative draft - Bańczerowski, Jerzy; Oueslati, Jamila (Scripta Neophilologica Posnaniensia, 2020)
Brought up for discussion are problems of general and particular mor(pho)phonology. First, some linguistic terms are clarified, and the status of morphophonology as a linguistic subdiscipline is considered. The particular morphophonological part, referring to Modern Standard Arabic (MSA) and Tunisian Arabic (TA), is topic oriented and it treats in succession: the structure of the verb forms, the relation of homoradicality (homolexicality) specifying the corresponding paradigmatization, and the intra- and interparadigmatic relations. In terms of the former of these relations the concept of morphoneme is defined, and among the latter morphophonological convergence and analogy as well as thematogen homoaffixality are distinguished. Finally, the dynamics of morphophonological space, morphonemic and morphonic representations are touched upon.